2017
DOI: 10.1093/mnras/stx327
|View full text |Cite
|
Sign up to set email alerts
|

Superwind evolution: the young starburst-driven wind galaxy NGC 2782

Abstract: We present results from a 30 ksec Chandra observation of the important starburst galaxy NGC 2782, covering the 0.3-10 keV energy band. We find evidence of a superwind of small extent, that is likely in an early stage of development.We find a total of 27 X-ray point sources within a region of radius 2D 25 of the galaxy centre and which are likely associated with the galaxy. Of these, 13 are ULXs (L X 10 39 erg s −1 ) and a number have likely counterparts. The X-ray luminosities of the ULX candidates are 1.2 − 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…X-ray satellites including Chandra and XMM-Newton observatories have been used to observe highly ionized X-ray emitting hot phase of galactic winds, and also to constrain the hard X-ray emission directly from very hot winds driven by supernova (SN) explosions [89][90][91][92][93]. Emission lines such as Hα, N II, O II, O III, and absorptions such as Na I D, K I, Mg II have been used to trace morphologies and velocities of warm, cool and cold outflows in galactic winds, including warm ionized [94][95][96][97][98][99][100][101][102], neutral atomic [19,[103][104][105][106][107][108][109][110], molecular [111][112][113][114][115][116][117][118], and dust [119][120][121][122][123][124] outflows.…”
Section: Multiphase Structurementioning
confidence: 99%
“…X-ray satellites including Chandra and XMM-Newton observatories have been used to observe highly ionized X-ray emitting hot phase of galactic winds, and also to constrain the hard X-ray emission directly from very hot winds driven by supernova (SN) explosions [89][90][91][92][93]. Emission lines such as Hα, N II, O II, O III, and absorptions such as Na I D, K I, Mg II have been used to trace morphologies and velocities of warm, cool and cold outflows in galactic winds, including warm ionized [94][95][96][97][98][99][100][101][102], neutral atomic [19,[103][104][105][106][107][108][109][110], molecular [111][112][113][114][115][116][117][118], and dust [119][120][121][122][123][124] outflows.…”
Section: Multiphase Structurementioning
confidence: 99%
“…As described above, however, the present IR spectra do not show clear evidence of an AGN. Only recent X-ray observations indicate the presence of a low-luminosity AGN (Tzanavaris & Georgantopoulos 2007;Bravo-Guerrero & Stevens 2017). Knierman et al (2013) detected a number of star cluster candidates (SCCs) both in the western and eastern tails.…”
Section: Ngc 2782mentioning
confidence: 99%
“…Gas motion in the central part of the galaxy is studied in detail by interferometric CO observations (Hunt et al 2008). NGC 2782 was originally classified as a Seyfert galaxy, but no direct sign of AGN had been obtained (Boer et al 1992) until recent X-ray observations found clear evidence for the presence of a low-luminosity AGN (Tzanavaris & Georgantopoulos 2007;Bravo-Guerrero & Stevens 2017). Star-formation in the tidal tails was studied extensively based on observations of CO (J=1-0), Hα, and [C II] 158 µm (Smith et al 1999;Knierman et al 2013).…”
Section: Introductionmentioning
confidence: 99%